Understanding and Reducing Disability in Older Adults Following Critical Illness*. Issue 6 (June 2015) - Brummel, Nathan E.; Balas, Michele C.; Morandi, Alessandro; Ferrante, Lauren E.; Gill, Thomas M.; Ely, E. Wesley
Abstract : Objective: To review how disability can develop in older adults with critical illness and to explore ways to reduce long-term disability following critical illness. Data Sources: We searched PubMed, CINAHL, Web of Science and Google Scholar for studies reporting disability outcomes (i.e., activities of daily living, instrumental activities of daily living, and mobility activities) and/or cognitive outcomes among patients treated in an ICU who were 65 years or older. We also reviewed the bibliographies of relevant citations to identify additional citations. Study Selection: We identified 19 studies evaluating disability outcomes in critically ill patients who were 65 years and older. Data Extraction: Descriptive epidemiologic data on disability after critical illness. Data Synthesis: Newly acquired disability in activities of daily living, instrumental activities of daily living, and mobility activities was commonplace among older adults who survived a critical illness. Incident dementia and less severe cognitive impairment were also highly prevalent. Factors related to the acute critical illness, ICU practices, such as heavy sedation, physical restraints, and immobility, as well as aging physiology, and coexisting geriatric conditions can combine to result in these poor outcomes. Conclusions: Older adults who survive critical illness have physical and cognitive declines resulting in disability at greater rates than hospitalized, noncritically ill and community dwelling older adults. Interventions derived from widely available geriatric care models in use outside of the ICU, which address modifiable risk factors including immobility and delirium, are associated with improved functional and cognitive outcomes and can be used to complement ICU-focused models such as the ABCDEs. Abstract : Supplemental Digital Content is available in the text.